2022
DOI: 10.1007/s00122-022-04239-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a key genomic region on chromosome 6 for resistance to Fusarium stalk rot in tropical maize

Abstract: Key message A key genomic region was identified for resistance to FSR at 168 Mb on chromosome 6 in GWAS and haplotype regression analysis, which was validated by QTL mapping in two populations. Abstract Fusarium stalk rot (FSR) of maize is an economically important post-flowering stalk rot (PFSR) disease caused by Fusarium verticillioides. The pathogen invades the plant individually, or in combination with other stalk rot pathogens or secondary colonizers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…1 at 250-251 Mb in all populations of CML, DTMA, and CominbedPOP in this study, which was the only one of the 13 regions that overlapped in all populations. Similarly, one recent study on FSR also detected a stable genomic region on chromosome 6 at 168Mb, which used a CAAM panel assembled at CIMMYT, consisting of 342 tropical/sub-tropical inbred lines bred in Asia(Rashid et al 2022). Interestingly, in this present study, near this region (162-168 Mb), six SNPs were detected by the mixed linear model in GWAS using the populations from the present study (Supplementary Table3).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…1 at 250-251 Mb in all populations of CML, DTMA, and CominbedPOP in this study, which was the only one of the 13 regions that overlapped in all populations. Similarly, one recent study on FSR also detected a stable genomic region on chromosome 6 at 168Mb, which used a CAAM panel assembled at CIMMYT, consisting of 342 tropical/sub-tropical inbred lines bred in Asia(Rashid et al 2022). Interestingly, in this present study, near this region (162-168 Mb), six SNPs were detected by the mixed linear model in GWAS using the populations from the present study (Supplementary Table3).…”
supporting
confidence: 73%
“…A key genomic region on Chr. 6 at 168 Mb conferring FSR resistance, with the PVE values ranging from 6.16 to 8.38%, was identi ed by a GWAS analysis recently, which was further validated by linkage mapping in two F 2:3 populations (Rashid et al 2022). The candidate gene conferring FSR resistance in this crucial region is annotated as a nucleic acid binding protein, playing an integral part in gene silencing pathways, and responding to diverse abiotic stress tolerances in maize.…”
Section: Introductionmentioning
confidence: 82%
“…In maize disease resistance studies, GWAS has been successfully applied to identify QTL or genomic regions associated with resistance to vital maize diseases, including Fusarium ear rot ( Yao et al., 2020 ), common rust ( Olukolu et al., 2016 ), gray leaf spot ( Kuki et al., 2018 ), northern corn leaf blight ( Ding et al., 2015 ), southern corn leaf blight ( Kump et al., 2011 ), rough dwarf ( Chen et al., 2015 ), maize dwarf mosaic disease caused by sugarcane mosaic virus ( Tao et al., 2013 ), and Fusarium stalk rot ( Liu et al., 2021 ; Rashid et al., 2022 ). However, literature on application of GWAS in Pythium stalk rot disease resistance identification is currently unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…We identified four SNPs (S4_ 153228905, S4_ 153228676, S4_ 153270388, and S4_ 153270407) associated with maize resistance to P. aristosporum in bin 4.06, consistent with the location range of stalk rot resistance genes Rpi1 and RpiX178-2 against P. inflatum ( Yang et al., 2005 ; Duan et al., 2019 ). A previous study indicated that a key genomic region at 168 Mb on chromosome 6 was associated with Fusarium stalk rot resistance using GWAS and haplotype regression ( Rashid et al., 2022 ). In this study, we identified a significantly associated SNP (S6_121809944) for PASR resistance in five models on chromosome 6 at 121 Mb.…”
Section: Discussionmentioning
confidence: 99%
“…[20], based on 165 maize inbred lines and 4666 SNP markers, performed genetic diversity analysis, GWAS, linkage analysis, and phenotypic analysis through the inoculation of stalk rot pathogen on maize plants in the field. For identification and validation of genomic regions associated with Fusarium stalk rot resistance, Rashid et al [21] used GWAS for 342 maize lines and 290,626 SNPs. The panel was screened for Fusarium stalk rot in three environments using standard artificial inoculation methodology.…”
Section: Introductionmentioning
confidence: 99%